1999
DOI: 10.1002/(sici)1097-4628(19990725)73:4<573::aid-app13>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diisocyanate isomer composition on properties and morphology of polyurethanes based on 4,4′-dicyclohexyl methane diisocyanate and mixed macrodiols (PDMS-PHMO)

Abstract: Three series of polyurethanes were prepared having 42 wt % hard segments based on 4,4Ј-dicyclohexyl methane diisocyanate (H 12 MDI) with trans,trans isomer contents in the 13 to 95 mol % range and 1,4-butanediol chain extender. The soft segments were based on macrodiols poly(hexamethylene oxide) (PHMO, MW 696), ␣,-bishydroxyethoxypropyl polydimethylsiloxane (PDMS, MW 940), and two mixed macrodiol compositions consisting of 80 and 20% (w/w) PDMS. H 12 MDI with 35, 85, and 95% trans,trans isomer contents were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Hence, the effects of the diisocyanate structure and symmetry on the morphology and tensile properties of PUs, polyurethaneureas, and PUrs has been addressed in various studies. For example, Adhikari et al and Saralegi et al both studied the influence of the symmetric trans - trans -4,4′-methylenebis(cyclohexyl isocyanate) (H 12 MDI) isomer ratio on the mechanical properties and microphase separation of PUs [ 23 , 24 ]. They found that microphase separation in the PUs increases due to a higher HS ordering.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the effects of the diisocyanate structure and symmetry on the morphology and tensile properties of PUs, polyurethaneureas, and PUrs has been addressed in various studies. For example, Adhikari et al and Saralegi et al both studied the influence of the symmetric trans - trans -4,4′-methylenebis(cyclohexyl isocyanate) (H 12 MDI) isomer ratio on the mechanical properties and microphase separation of PUs [ 23 , 24 ]. They found that microphase separation in the PUs increases due to a higher HS ordering.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics include but are not limited to the very low T g (−123 °C), good thermal and oxidative stability, satisfactory release properties, and excellent electrical insulation properties. , Jasna Djonlagić et al found that polyurethanes containing ethoxypropyl-poly­(dimethylsiloxane) macrodiol exhibited an excellent resistance to the fibrinogen adsorption and showed more favorable adsorption for albumin than that for fibrinogen in the competitive adsorption assay, suggesting their good hemocompatibility. However, the incompatibility of the nonpolar PDMS segments between hard segments resulted in a PUE with poor mechanical properties, such as low elongation. ,, Raju Adhikari et al found that the elongation at the break of the polyurethanes containing PDMS was about 310%. Many efforts have been made to synthesize PDMS-based polyurethanes with good mechanical properties, with the primary focus on the enhancement of the interfacial adhesion between the soft domains and the hard domains. , These techniques include mixing with polar oligomeric polyols (polyether or polyester), the introduction of polar groups to PDMS, and hard segment modifications.…”
Section: Introductionmentioning
confidence: 99%
“…These properties include an extremely low glass‐transition temperature ( T g ; −123°C), low surface tension, high flexibility, high permeability to gases, chemical inactivity, insulating stability, very good thermal stability, and UV stability 10–13. In the past, many studies were published in which PDMS was used as a component of PU to improve PU properties such as water resistance, flame resistance, and heat resistance 14–16. However, few studies on PDMS‐modified WBPUs and UV‐curable WBPUs have been reported recently 17…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] In the past, many studies were published in which PDMS was used as a component of PU to improve PU properties such as water resistance, flame resistance, and heat resistance. [14][15][16] However, few studies on PDMSmodified WBPUs and UV-curable WBPUs have been reported recently. 17 Shape-memory polymers (SMPs) are capable of changing their shape on exposure to a stimulus such as heat, electrical current, or photoenergy.…”
Section: Introductionmentioning
confidence: 99%